Signaling and contract cost under weak governance: Water service privatization in Metro-Manila, Philippines - Raul V. Fabella (University of the Philippines, School of Economics (UPSE), 2012)
Many supply contracts between the state and private agents in a developing country are cost-re-imbursement variety and are rolled out under weak and unreliable governance. The latter has to be provided for through higher supply cost. The state in turn can lower the contract cost by providing verifiable credible commitments of its intentions. We show using a modified the Laffont-Tirole cost-reimbursement contract model that the more reliable is the state in respect to the delivery of its contractual obligations, the lower the cost of contracts to the state and society. We argue that the various actions taken by the Philippine government before the privatization of the water service in Metro Manila in 1997, viz., the substantial increase in the tariff, the reduction in the labor complement by 30% and the outsourcing of the dispute resolution mechanism to an international appeals panel, induced entry and aggressive bidding by the contenders that dramatically reduced the cost to the public of the water services concession contract in Metro Manila, Philippines.
Keywords: L33; I30; H57; 330; signaling; credible commitment; procurement contracts; weak governance; Wasserwirtschaft; Privatisierung; Rechtsdurchsetzung; Governance-Ansatz; Manila; Philippinen